STROKE: PATHOGENESIS, TRADITIONAL AND MODERN NEUROREHABILITATION STRATEGIES – A REVIEW OF CURRENT METHODS - Paweł Edyko; Zuzanna Przybyła; Katarzyna Andrzejewska; Wiktor Golus; Hubert Woźniak; Helena Szelka; Anna Maria Gęsińska; Krystian Czyżykowski; Alicja Babula; Bartosz Golis (International Journal of Innovative Technologies in Social Science, 2025)
Objectives: Stroke remains one of the leading causes of mortality and long-term disability worldwide. The objective of this review was to synthesize current evidence on the biological mechanisms underlying ischemic and hemorrhagic stroke and to evaluate the effectiveness of traditional and emerging neurorehabilitation strategies. Methods: A structured narrative review was conducted using major medical databases, including PubMed, Scopus, Web of Science, and Google Scholar. Additional sources were identified through manual reference screening. Studies examining pathophysiology and rehabilitation approaches in stroke were included and qualitatively analyzed. Results: Findings indicate that acute energy failure, excitotoxicity, oxidative stress, and neuroinflammation are key pathophysiological drivers of early neuronal damage, while phases of neuroplastic reorganization strongly influence recovery potential. Traditional rehabilitation approaches remain central due to strong evidence supporting their effectiveness in motor relearning, however, limitations related to therapy intensity and patient engagement persist. Emerging modalities—such as robotic-assisted training, virtual reality–based interventions, telerehabilitation, non-invasive brain stimulation, and vagus nerve stimulation—show increasing evidence for enhancing training dosage, modulating cortical excitability, and enabling individualized therapy. Conclusions: Integrating conventional rehabilitation with modern technological and neuromodulatory interventions appears to offer the most effective strategy for optimizing functional outcomes and supporting sustainable long-term recovery in stroke survivors.